Frequency of Hypocalcemia after Thyroid Surgery - Muhammad Bilal Butt, Sana Fayyaz, Quratulain, Varda Balouch, Waleed Sultan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to determine the prevalence of hypocalcemia among patients after thyroid surgery. Study Design: Descriptive study/ Cross-sectional Place and Duration: The study was conducted at the surgical department of Mayo Hospital, Lahore for the duration of eighteen months from July 2020 to December 2021. Methods: Fifty-five male and female subjects participated in this research. Patients ranged in age from 17 to 62 years. After obtaining written permission from the patient, demographic information such as age, sex, BMI, and tumors type was collected. Contralateral lobe cancer was also shown to be a problem. Before surgery and on the first post-operative day, the blood calcium levels of the patients were measured. Patients who received a full thyroidectomy were evaluated for signs of hypocalcemia. Analysis was performed using SPSS 22.0. Results: Among 55 patients, majority of the cases were females 30 (54.5%) were females and the rest were males 25 (45.5%). The patients mean age was 37.16±14.52 years and had mean BMI 24.45±6.62 kg/m2. Papillary cancer was the most common tumor found in 42 (76.4%) cases, followed by follicular cancer in 9 (16.4%) case and 4 (7.3%) cases had hurthle cell carcinoma. We found frequency of hypocalcemia in 14 (25.5%) cases. Among 14 patients of hypocalcemia 10 (71.4%) were females and 4 (38.6%) were males. Retrosternal of goiter found in 5 (35.7%) cases and no retrosternal extension found in 9 (64.3%) case. Post-operative other complications among all cases were seroma, transient hoarseness of voice and neck hematoma. Conclusion: In this study we found higher frequency of hypocalcemia in 25.5% cases after thyroid surgery. Majority of the cases were females and had no retrosternal extension. Except hypocalcemia other complications among all cases were seroma, transient hoarseness of voice and neck hematoma.